2005
DOI: 10.1162/0899766054026639
|View full text |Cite
|
Sign up to set email alerts
|

How Close Are We to Understanding V1?

Abstract: A wide variety of papers have reviewed what is known about the function of primary visual cortex. In this review, rather than stating what is known, we attempt to estimate how much is still unknown about V1 function. In particular, we identify five problems with the current view of V1 that stem largely from experimental and theoretical biases, in addition to the contributions of nonlinearities in the cortex that are not well understood. Our purpose is to open the door to new theories, a number of which we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
260
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(282 citation statements)
references
References 113 publications
11
260
2
1
Order By: Relevance
“…Although at present we cannot disentangle the contribution from cortical feedback and lateral interaction, we believe that the fact that such information is transmitted at all from stimulated to nonstimulated regions highlights the ubiquitous role that context might play in shaping the activity of all neurons in early vision. Indeed, several authors recently have pointed out that, to increase our understanding of V1 beyond the best current models, a deeper consideration of the role of context (both spatial and temporal) and of how such contextual information is transmitted is required (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Although at present we cannot disentangle the contribution from cortical feedback and lateral interaction, we believe that the fact that such information is transmitted at all from stimulated to nonstimulated regions highlights the ubiquitous role that context might play in shaping the activity of all neurons in early vision. Indeed, several authors recently have pointed out that, to increase our understanding of V1 beyond the best current models, a deeper consideration of the role of context (both spatial and temporal) and of how such contextual information is transmitted is required (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…What is interesting about this feedback is that it is between functional areas, is adaptive, and often changes as a function of task. It is therefore clear that feedback is a key component of visual analysis, but what is its compu-tational role (Olshausen & Field, 2005) and at what stage does it occur in order to produce observed behavior?…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the why of the physiology, it excludes descriptive models concerning what and how, e.g., models of the center-surround receptive fields of the retinal ganglion cells, or mechanistic models of how orientation tuning in V1 develops. Useful reviews of early vision with related or different emphases and opinions can be found in, e.g., Atick (1992), Meister andBerry 1999, Simoncelli andOlshausen (2001), Lennie (2003), Lee (2003), and Olshausen and Field (2005 Figure 1: Process flow diagram illustrating two bottom-up strategies proposed for early vision to reduce data rate through information bottlenecks -(1) data compression with minimum information loss, and, (2) creating a saliency map to enable lossy selection of information.…”
Section: Introduction and Scopementioning
confidence: 99%